Frozen Elephant Trunk for Acute Type B Dissection Involving the Distal Arch in the Hybrid Repair Era - Qi, Rui-Dong; Zhu, Jun-Ming; Liu, Yong-Min; Chen, Lei; Li, Cheng-Nan; Xing, Xiao-Yan; Zhang, Nan; Sun, Li-Zhong (The Annals of thoracic surgery, 2018)
Hybrid repair of complicated acute type B aortic dissection (ATBAD) with aortic arch involvement is associated with a high rate of endoleak, stroke, and retrograde aortic dissection. Optimal management of this lesion remains uncertain. In this hybrid repair era, surgical results of ATBAD with distal aortic arch involvement using a frozen elephant trunk procedure with transposition of the left subclavian artery (LSCA) to left common carotid artery (LCCA) is reported. From April 2011 to April 2016, 53 patients with complicated ATBAD with distal aortic arch involvement underwent a frozen elephant trunk procedure with LSCA-LCCA transposition. Preoperative organ malperfusion included renal ischemia in 10 subjects, renal infarction in 2, lower limb ischemia in 6, and visceral ischemia in 5. There was no inhospital death. Continuous renal replacement therapy was required in 1 patient. Permanent neurologic injury was observed in 1 patient and temporary neurologic dysfunction in 1 patient. Ischemia of the lower limb and viscera was ameliorated after frozen elephant trunk implantation. During follow-up, thoracoabdominal aortic replacement was required in 1 patient, and the Wheat procedure in 1 other patient. The patency rate of the anastomotic site between the LSCA and LCCA was 100%, and shrinkage of the descending aorta occurred in 90.4% of patients (47 of 52) as demonstrated by computed tomography. Open repair of ATBAD with distal aortic arch involvement using the frozen elephant trunk procedure with LSCA-LCCA transposition obtained satisfactory outcomes. Avoidance of complications using hybrid repair, good postoperative recovery, and a low prevalence of late reintervention were achieved. The satisfactory results favored this technique for this lesion in this hybrid repair era.